The first publication of M.M. Agarkov (1914) - K.M. Arslanov; D.R. Miftakhutdinova; A.S. Pugacheva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relevance of the paper is in the increased interest of the legal community in the works of the classics of Russian civil law. The purpose of the paper is to reproduce the first publication of M.M. Agarkov, one of the patriarchs of modern legal science and a representative of the Kazan School of Civil Law. A wide audience gets the opportunity to become acquainted with the work of M.M. Agarkov, which was of a review character, reflected the views of scientists on the nature of the labor contract (personal hiring) in accordance with the current French law and jurisprudence, and also indicated certain gaps in the legal regulation of this treaty in connection with the development of public relations. The material illustrating the formation of the Kazan School of Civil Law, a distinctive feature of which consisted in striving for an original explanation of legal conflicts taking into account foreign legal experience, has been introduced into scientific circulation.